Methodological Bases of Research of the Content of School Social Studies Education in Ukraine of the XX Century - Volodymyr Areshonkov (Pedagogical Discourse, 2014)
The author of the article determined methodological bases of studying the content of school pulic identifying education of Ukraine of the XX century. The material of the scientists on this problem has been analyzed. The content of the subject approach, basic directions of working out theoretical bases of the content of education have been determined. Scientific approaches to the determination of the content of education have been grounded, their peculiarities have been revealed. The main units of the structure of content of pulic identifying education on subject level (monosubject or polysubject) the subject knowledge, ways of educational activity have been singled out. The conclusion has been determined; it goes that under the conditions of complex of methodological approaches: system, structural-functional, specific-historical, axiological, paradigm, it is possible to consider the content of school pulic identifying education of the XX century as culturological phenomenon and as a model of social order, which is contextual side of education in the subject of didactics.